Healing Potential of Picrorhiza kurroa (Scrofulariaceae) rhizomes against indomethacin-induced gastric ulceration: a mechanistic exploration. - Banerjee, Debashish (BioMed Central, 2008)
BACKGROUND: The present study was undertaken to evaluate the potential of the rhizomes of the Indian medicinal plant, Picrorhiza kurroa in healing indomethacin-induced acute stomach ulceration in mice and examine its capacity to modulate oxidative stress and the levels of prostaglandin (PGE(2)) and EGF during the process. METHODS: Male swiss albino mice, ulcerated with indomethacin (18 mg/kg, p. o., single dose) were treated up to 7 days with different doses of the methanol extract of P. kurroa rhizomes (designated as PK). The healing capacity of the most effective dose of PK (20 mg/kg, p. o. × 3 d) was compared with that of omeprazole (Omez) (3 mg/kg, p. o. × 3 d). The effects of the drug-treatment for one and three days on the biochemical parameters were assessed by comparing the results with that of untreated mice of the 1(st )and 3(rd )day of ulceration. The stomach tissues of the mice were used for the biochemical analysis. RESULTS: The macroscopic indices revealed maximum ulceration on the 3(rd )day after indomethacin administration, which was effectively healed by PK. Under the optimized treatment regime, PK and Omez reduced the ulcer indices by 45.1% (P < 0.01), and 76.3% respectively (P < 0.001), compared to the untreated ulcerated mice. Compared to the ulcerated untreated mice, those treated with PK for 3 days showed decreased the levels of thiobarbituric acid reactive substances (TBARS) (32.7%, P < 0.05) and protein carbonyl (37.7%, P < 0.001), and increased mucin (42.2%, P < 0.01), mucosal PGE(2 )(21.4%, P < 0.05), and expressions of COX-1 and 2 (26.9% and 18.5%, P < 0.05), EGF (149.0%, P < 0.001) and VEGF (56.9%, P < 0.01). Omez reduced the TBARS (29.4%, P < 0.05), and protein carbonyl (38.9%, P < 0.001), and increased mucin (38.3%, P < 0.01), without altering the other parameters significantly. CONCLUSION: PK (20 mg/kg, p. o. × 3 days) could effectively heal indomethacin-induced stomach ulceration in mice by reducing oxidative stress, and promoting mucin secretion, prostaglandin synthesis and augmenting expressions of cyclooxygenase enzymes and growth factors.